Evaluación del suero lácteo en la producción de biomasa y lípidos en la microalga chlorella vulgaris a escala de laboratorio (2017)
In order to evaluate the potential use of microalgae to obtain lipids through the implementation of residual substrates of the industries, the influence of whey in the production of microalgae and lipid biomass and adapted photobioreactors were evaluated in an incubator that allows to generate the conditions and to cultivate the microalgae in laboratory scale. The microalgae were cultured in adapted photobioreactors using culture medium composed of foliar fertilizer (Foliagro) and enriched culture medium composed by culture medium and whey; in which the relationships between the components of the enriched culture medium were varied in 13 pre-experiment tests and the highest cell concentration was selected. Cell growth was quantified by counting in the neubauer chamber for about 20 days where a cell concentration of 1.11x106 (cells / mL) was obtained. The biomass treatment process consisted of the initial separation of the liquid and solid phases by the centrifugation method, after being dried at 40 ° C in a drying oven, obtaining a volumetric productivity in dry weight of 1.52 x 10-3 g / mL compared to the culture fed with the culture medium, which was 7.5 x 10-4 g / mL being lower, which shows that the medium enriched with whey had a Better yield of dry biomass.